Spatial variability of the noise generated by a portable harvester in a coffee field - Ferraz, Gabriel Araújo e Silva; da Silva, Flavio Castro; Nunes, Rodrigo Alencar; Ponciano, Patricia Ferreira (Coffee Science - ISSN 1984-3909, 2014)
The aim of this work was to evaluate the portable harvester noise spatial distribution operating in a coffee field and to identify the workers salubrity zones. The experiment was developed in a coffee field of Acaiá Cerrado MG-1474 cultivar planted in the spacing of 3.0 m between rows and 0.6 m between plants. It is located at the Engineering Department of the Federal University of Lavras. It was used in this study a two-stroke portable harvester with 1.3 cv (25,4 cm³) and a digital decibel meter to collect the noise levels distributed in a regular sample grid of 3.0 x 5.0 m around the harvester in operation. The noise spatial dependence was evaluated by variogram adjusts and krigging interpolation. The variogram was adjusted based on residual maximum likelihood and by a spherical model. The analyses of these data by the geostatístics techiniques allowed to characterize the spatial distribution of the produced noise and to create a noise map by krigging that will contribute to crate salubrity zones to workers involved on coffee harvest.